Making shape memory polymers reprocessable and reusable by a simple chemical method - Ahmad, M. (2013)
We have found that a group of shape memory polymers in the polyurethane family can be recycled for new use when their parent polymeric chains are fabricated with a small percentage of polyethylene glycol, and the products are subsequently reprocessed in N,N-dimethylformamide (DMF), a very commonly used organic solvent.